Pemetrexed sensitizes human lung cancer cells to cytotoxic immune cells. Issue 6 (22nd April 2020) - Okimoto, Tamio; Kotani, Hitoshi; Iida, Yuichi; Koyanagi, Akira; Tanino, Ryosuke; Tsubata, Yukari; Isobe, Takeshi; Harada, Mamoru
Abstract: Pemetrexed (PEM) is a useful drug that can be combined with immune checkpoint blockade therapy for treatment of patients with advanced non–small‐cell lung cancer (NSCLC). However, its effects on anti–cancer immunity, especially the sensitivity of NSCLC cells to cytotoxic immune cells, have not been fully investigated. In this study, we examined the effects of PEM on the sensitivity of human NSCLC cells to two different types of cytotoxic immune cells. Pre‐treatment with PEM increased the sensitivity of two NSCLC cell lines, PC9 and A549, to activated T cells and natural killer (NK) cells, and decreased the expression of anti–apoptotic proteins, including XIAP and Mcl‐1. In addition, PEM treatment increased the cell surface expression of programmed death‐ligand 1 (PD‐L1) on PC9 cells. PEM‐induced upregulation of PD‐L1 on PC9 cells was at least partially ascribed to activation of ERK and the NFκB pathway. In contrast, PEM treatment increased the expression of UL16‐binding proteins (ULBP), ligands for the NKG2D NK receptor, on PC9 and A549 cells, as well as the induction of senescence. Although the addition of anti–programmed cell death 1 antibody showed no effect on the sensitivity of PEM‐treated PC9 and A549 cells to activated T cells, that of anti–NKG2D antibody decreased the enhanced sensitivity of PEM‐treated A549 cells to NK cells. These results indicate that PEM can effectively sensitize human NSCLC cells to cytotoxic immune cells while modulating the expression of immune‐regulatory molecules. Abstract : Pemetrexed treatment induces the mRNA expression of NKG2D ligands in human lung cancer cells.